P64 Experiences of men who have sex with men (MSM) when engaging in the partner notification process three months following a HIV diagnosis. (18th May 2015) - Roberts, Jonathan; Nixon, Eileen; Perry, Nicky; Sheriff, Nigel; Richardson, Daniel
Abstract : Background/introduction: Partner Notification (PN) can be used as a tool for detecting undiagnosed HIV, but fear of stigma around disclosure and concerns about lack of confidentiality are potential barriers and may deter newly diagnosed individuals from engaging in this activity. Aim(s)/objectives: To identify facilitating or prohibiting factors for HIV infected MSM when undertaking partner notification following HIV diagnosis. Methods: Semi structured interviews with ten newly diagnosed HIV MSM. All were recruited from a local NHS HIV outpatient service. Interviews were recorded verbatim and framework analysis was used to analyse the data. Results: Facilitating factors: There was a general acceptance and an awareness of necessity to initiate PN with immediacy, given the potential risk of onward transmission. Most participants expressed a "social responsibility "to inform partners of their HIV status if contactable, with a preference for disclosure through face to face contact if regular partner/s, but acknowledged that provider referral would be a useful option for non-regular or casual partners. Through "self-assessment of risk" most were able to identify the potential source of acquisition, and partners that could be "at risk" or infected. Prohibiting factors: Concerns about stigmatisation and criminalisation around disclosure of status remain key concerns, but participants particularly valued the support received from HCPs around addressing all aspects of PN. Discussion/conclusion: Important themes were identified that should be considered when supporting individuals in disclosing their HIV status to partners, providing a deeper understanding of the PN process from a patient's perspective and generating ideas that should be considered in future service provision and HIV PN studies.